In Situ Quantitative Raman Detection of Dissolved Carbon Dioxide and Sulfate in Deep‐Sea High‐Temperature Hydrothermal Vent Fluids. (22nd June 2018) - Li, Lianfu; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Xi, Shichuan; Wang, Bing; Cao, Lei; Lian, Chao; Yan, Jun
Abstract: Carbon dioxide emitted from hydrothermal vents, as an important part of the global carbon cycle, can directly affect hydrothermal ecosystems. However, traditional chemical analysis methods cannot directly measure the concentrations of dissolved CO2 in high‐temperature hydrothermal fluids. Although in situ mass spectrometry has been applied to the measurements of deep sea, it cannot be used to detect high‐temperature fluids. In this study, an in situ Raman quantitative method for measuring dissolved CO2 suitable for a hydrothermal environment is established. The Raman relative intensity of CO2 displayed a linear relationship with increasing concentration of CO2 under the investigated conditions (up to 300°C and 40 MPa), allowing this in situ measurement method to be applied to most hydrothermal fields worldwide. Moreover, we find that the quantitative calibration curve for SO 4 2 − for high‐temperature and high‐pressure conditions is identical to that of SO 4 2 − for room temperature and atmospheric pressure. The concentrations of CO2 in mid‐Okinawa Trough hydrothermal fluids determined by in situ Raman measurement are 188.4–532.3 mmol/kg, which are about 3 times higher than those obtained by traditional sampling methods (59–198 mmol/kg). However, the concentrations of SO 4 2 − calculated from in situ Raman spectra were near zero, indicating that the in situ Raman measurement avoids hydrothermal fluids contaminated with seawater. Key Points: The in situ concentrations of CO2 and SO 4 2 − of the high‐temperature hydrothermal fluids in the mid‐Okinawa trough were obtained for the first time by the deep ocean in situ Raman system Raman quantitative models suitable to the deep ocean in situ Raman system to determine the contents of dissolved CO2 and SO 4 2 − at 0–300°C, 0–40 MPa conditions were established The max‐concentration of dissolved CO2 in the mid‐Okinawa trough hydrothermal fluids was 532.3 mmol/kg, which was much higher than that of gas‐tight samples